Surface expression of CD39 identifies an enriched Treg‐cell subset in the rheumatic joint, which does not suppress IL‐17A secretion. Issue 10 (25th August 2014) - Herrath, Jessica; Chemin, Karine; Albrecht, Inka; Catrina, Anca I.; Malmström, Vivianne
<x xml:space="preserve">Abstract</x> Treg cells are important for the maintenance of self‐tolerance and are implicated in autoimmunity. Despite enrichment of Treg cells in joints of rheumatoid arthritis (RA) patients, local inflammation persists. As expression of the ATP‐hydrolyzing enzymes CD39 and CD73 and the resulting anti‐inflammatory adenosine production have been implicated as an important mechanism of suppression, we characterized FOXP3+ Treg cells in blood and synovial fluid samples of RA patients in the context of CD39 and CD73 expression. Synovial FOXP3+ Treg cells displayed high expression levels of rate‐limiting CD39, whereas CD73 was diminished. FOXP3+CD39+ Treg cells were also abundant in synovial tissue. Furthermore, FOXP3+CD39+ Treg cells did not secrete the proinflammatory cytokines IFN‐γ and TNF after in vitro stimulation in contrast to FOXP3+CD39− T cells. FOXP3+CD39+ Treg cells could be isolated by CD39 and CD25 coexpression, displayed a demethylated Treg‐specific demethylated region and coculture assays confirmed that CD25+CD39+ T cells have suppressive capacity, while their CD39− counterparts do not. Overall, our data show that FOXP3+CD39+ Treg cells are enriched at the site of inflammation, do not produce proinflammatory cytokines, and are good suppressors of many effector T‐cell functions including production of IFN‐γ, TNF, and IL‐17F but do not limit IL‐17A secretion.